From gut to proteomics: the impact of Roseburia intestinalis on post-translational modifications in colorectal cancer - Li, Lu; Zhang, Yong; Wu, Qianqian; Jin, Ziyu; Xia, Hongbing; Wu, Huili; Li, Kunkun; Wang, Lihong (Frontiers in Oncology, 2025)
BackgroundColorectal cancer (CRC) represents a significant global health challenge. Gut microbiota imbalance and abnormal chromatin modifications play critical roles in the progression of CRC. However, the mechanisms by which they exert their influences, particularly the involvement of Roseburia intestinalis (R.i)-mediated post-translational modifications (PTMs), remain inadequately understood. This study aims to explore global acylase change map induced by R.i in CRC cells.MethodsThe 4D-Fast DIA quantitative acetylated modified proteome and the 4D-Fast DIA quantitative lactated modified proteome combined with proteomics were used to detect CRC cells (HCT116) co-cultured with R.i. Cell proliferation was evaluated by the Cell Counting Kit-8 (CCK-8) assay and colony formation assay.ResultsIn this study, we verified elevated levels of lactylation in CRC tumor tissues and cells. Intervention with R.i was shown to induce a reduction in cellular lactylation levels while increasing acetylation levels. A total of 6,134 acetylation (Kac) sites were identified across 3,037 acetylated proteins, and 7,882 lactylation (Lac) sites were identified among 2,386 lactylated proteins. Notably, the subcellular distribution of proteins modified at Kac and Lac sites exhibited distinct patterns. Additionally, there were differences in specific sequence motifs surrounding acetylated or lactylated lysine residues. To further investigate the differentially expressed proteins involved in Kac and Lac modifications, we conducted enrichment analyses using Biological Process and the Kyoto Encyclopedia of Genes and Genomes. The acetylome profiling identified significant enrichment of differentially expressed proteins in several critical metabolic pathways, including: Glycolysis, Lipid metabolism, Pyruvate metabolism, Glycerophospholipid metabolism. Concurrently, lactylome analysis demonstrated distinct protein enrichment in: Glycolysis, Galactose metabolism, Pentose phosphate pathway, Non-homologous end-joining. Notably, glycolysis emerged as the principal convergent pathway between acetylation and lactylation modifications, suggesting its central regulatory role in metabolic reprogramming under these PTMs.ConclusionsOur study reveals a previously unrecognized mechanism by which R.i orchestrates metabolic-translational post-translational modification crosstalk in CRC through bidirectional modulation of protein markers. These findings offer insights into the underlying mechanisms that may influence CRC progression.